Unlocking Potentials: Exploring Awareness, Utilization, and Perceptions related to Benefits and Challenges of Artificial Intelligence in Research - A Study amongst Aspiring Healthcare Professionals of Islamabad - Amjad, Tahira; Ikram, Owais Mahmood; Akif, Murtaza; Sajid, Hafza; Sadiq, Rikza (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess level of awareness, utilization pattern, and perceptions regarding benefits and challenges of artificial intelligence in research among aspiring healthcare professionals in Islamabad.Study Design: Cross Sectional Analytical studyPlace and Duration of Study: Foundation University School of Health Sciences (FUSH), Islamabad from 25th May to 25th September 2024Methodology: A stratified random sample of 355 students was surveyed after ethical approval using structured Google Form. After informed consent, data were collected on demographics, AI awareness, utilization, benefits, challenges and training needs, and analyzed using SPSS v25. Chi-square, t-tests, correlation, and regression were applied (p ≤ 0.05).Results: Of 355, 327 responded, among these, 236 (72.2%) were generally aware of AI in research, though 209 (88.5%) had no formal AI training. The mean awareness score 10.44±3.19, with 174 (73.7%) showing adequate awareness. However, only 75 (31.8%) showed sufficient AI tool utilization (mean score 6.4±4.29). Popular AI platforms included ChatGPT, Grammarly, and Mendeley. A majority (68.2%) agreed that AI improves research efficiency. Key barriers included lack of training (54.6%), limited technological access (46.2%), 93.6% expressed willingness to use AI in future research. Significant associations were found between awareness, utilization, and demographic variables.Conclusion: Aspiring healthcare professionals in Islamabad showed high AI awareness but low utilization, with limited formal training. Positive perceptions prevailed despite concerns over plagiarism, data security, and technical understanding. Formal AI training remains essential for developing responsible, effective, and ethical use of AI in research